Pendampingan Kelompok Pedagang Olahan Dadih di Kota Bukittinggi - Amna Suresti; James Hellyward; Amrizal Anas; Rahmi Wati (Warta Pengabdian Andalas, 2019)
This article describes the results of the training, coaching and mentoring on producer Dadih groups in the District of Tilatang Kamang. This activity aims to: 1) increase the motivation of entrepreneurial partners; 2) increase the insight and knowledge of maintenance management buffaloes; 3) improve the ability of the partners to diversify into multiple product Dadih and 4) developing the marketing area. The results of this activity were: 1) increase the entrepreneurial spirit partner as efforts to support the development of the group; 2) Activity buffaloes maintenance management counseling can improve insight and knowledge in raising livestock breeder buffalo; 3) Training and the pilot was able to increase revenue diversification dadih and 4) The promotion and development of network marketing has been used as a marketing strategy to increase the production volume of business groups.